Advancement in COVID‐19 detection using nanomaterial‐based biosensors. Issue 1 (7th January 2023) - Truong, Phuoc Loc; Yin, Yiming; Lee, Daeho; Ko, Seung Hwan
Abstract: Coronavirus disease 2019 (COVID‐19) pandemic has exemplified how viral growth and transmission are a significant threat to global biosecurity. The early detection and treatment of viral infections is the top priority to prevent fresh waves and control the pandemic. Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has been identified through several conventional molecular methodologies that are time‐consuming and require high‐skill labor, apparatus, and biochemical reagents but have a low detection accuracy. These bottlenecks hamper conventional methods from resolving the COVID‐19 emergency. However, interdisciplinary advances in nanomaterials and biotechnology, such as nanomaterials‐based biosensors, have opened new avenues for rapid and ultrasensitive detection of pathogens in the field of healthcare. Many updated nanomaterials‐based biosensors, namely electrochemical, field‐effect transistor, plasmonic, and colorimetric biosensors, employ nucleic acid and antigen–antibody interactions for SARS‐CoV‐2 detection in a highly efficient, reliable, sensitive, and rapid manner. This systematic review summarizes the mechanisms and characteristics of nanomaterials‐based biosensors for SARS‐CoV‐2 detection. Moreover, continuing challenges and emerging trends in biosensor development are also discussed. Abstract : Interdisciplinary advances in nanomaterials and biotechnology, such as nanomaterials‐based biosensors, have opened new avenues for rapid and ultrasensitive detection of pathogens in the field of healthcare. Many updated nanomaterials‐based biosensors, namely electrochemical, field‐effect transistor, plasmonic, and colorimetric biosensors, employ nucleic acid and antigen–antibody interactions for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) detection in a highly efficient, reliable, sensitive, and rapid manner. This systematic review summarizes the mechanisms and characteristics of nanomaterials‐based biosensors for SARS‐CoV‐2 detection. Moreover, continuing challenges and emerging trends in biosensor development are also discussed.